Dogs, Ducks, and Dissent— A “Priest Play" on Tour in Ireland - Barrett, John (FOCUS: Papers in English Literary and Cultural Studies, 2024)
For the past few years my research interest has been in the area of audience response in the theatre. What makes an audience engage with the action on stage and what makes them disengage? Why will different types of audience react in different ways, or give widely different responses on different nights? I select a certain number of plays that are of different style and genre and I attend each of these a number of times, on different days of the week, different stages in the run, and, as far as possible, with different types of audience—e.g. matinéé audiences, audiences dominated by older or younger groups, by school-leavers, by American tourists.